2006
DOI: 10.2341/05-69
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Clinical Trial on the Efficacy of a New Bleaching Lacquer for Self-application

Abstract: It can be concluded that the new bleaching lacquer is efficacious; however, a double application does not seem to be obligatory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
2
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 18 publications
0
24
2
6
Order By: Relevance
“…[1] This is a result of the excellent aesthetic properties of these fillings, as well as health concerns regarding mercury release from amalgam fillings. [2] Therefore, the relation of filler properties to composite characteristics, such as radiopacity, [3] tensile strength, [4] hardness, [5] shrinkage, [6] wear, [2] and transparency [1] have been intensely studied in the last few years.…”
Section: Introductionmentioning
confidence: 99%
“…[1] This is a result of the excellent aesthetic properties of these fillings, as well as health concerns regarding mercury release from amalgam fillings. [2] Therefore, the relation of filler properties to composite characteristics, such as radiopacity, [3] tensile strength, [4] hardness, [5] shrinkage, [6] wear, [2] and transparency [1] have been intensely studied in the last few years.…”
Section: Introductionmentioning
confidence: 99%
“…Several laboratory and clinical studies have demonstrated carbamide peroxide or hydrogen peroxide bleaching solutions to be effective in whitening of discoloured teeth [2,4,6,16,26,27]. Thereby, efficacy might be related to the concentration of the active bleaching ingredient, the application time of the agents and the potential to penetrate dental hard tissues [10,15,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The substantial increase of lightness and decrease of chroma observed directly after bleaching is, however, often followed by a decrease of whitening in the post-bleaching period indicating that the bleaching effect might not be stable over time. After an initial reduction of lightening possibly due to rehydration processes in the first weeks after bleaching [17,19,26] a further colour regression towards baseline shades might occur. Two-year evaluation of nonvital tooth whitening revealed a 19% reduction compared to tooth colour directly after bleaching [4].…”
Section: Introductionmentioning
confidence: 99%
“…Bunun nedeni, renk tonunun rehidratasyona bağlı olarak bu sürede nihai değerine ulaştığı görüşüdür. 18 Beyazlatma tedavilerinde geri dönüş (relaps) değerlendirmesi için beyazlatmadan 6 ay sonra ve beyazlatmadan 1 yıl sonra ölçümler yapılmıştır. Beyazlatma tedavisinden 6 ay sonra değerlendirme, renklenmede geri dönüşün belirlenmesi için Amerikan Diş Hekimleri Derneği tarafından tavsiye edilen minimum süredir.…”
unclassified